The effects of age on the worker capacity and mechanisation on the task demands in a South African manufacturing industry - Bezuidenhout, Samantha Catherine (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2014)
The focus of the study was two-fold, firstly to determine the effect of age on the capacity of manual materials handling workers and secondly to determine the effect of increasing task mechanisation on the workers' responses to task demands. The first component of this study, namely Part I, 101 male and 12 female 'unskilled' manual workers "“ of various ages "“ from a brick manufacturing industry were assessed. Anthropometric, health and strength factors were measured to improve the understanding of the South African manual worker capacity and more specifically, the effect of age on this capacity. Data collection was done between 7.30am and 9.30am in a laboratory-type setting on-site. Anthropometric characteristics (including body mass index, waist to hip ratio, waist circumference and body fat percentage) provided information on the state of obesity and the impact of age in the South African context. Linked to this, the health factors (including blood pressure, resting heart rate and a self-reported questionnaire) provide an extra snapshot of the disease profile in South Africa, and could potentially influence other capacity factors. Isometric strength capacities (of eight different areas, namely: back, leg, bicep, shoulder, pinch, pinch and pull) demonstrated whether South African manual workers show the same decline in strength with aging as seen in industrially advanced countries. The second component of the study, Part II, was performed in situ and measured the workers' responses to task demands of three brick palletising tasks, one manual (n=21) and two with increasing mechanisation (n=12 each). Spinal kinematics, joint forces and working heart rate were assessed on normal work days during a 30-lift duration and body discomfort measures were taken at the start, middle and end of the work-shift. Spinal kinematics were measured dynamically using a lumbar motion monitor, whereas the spinal forces were estimated using the three dimensional static strength prediction program. The worker capacity results showed that waist to hip ratio, waist circumference and body fat percentage increased significantly with aging, whereas body mass index was not affected by age. All body morphology values were within 'normal' ranges. Although diastolic blood pressure increased significantly with age, systolic was not affected significantly by age. Both groups, however, showed an increasing prevalence of hypertension with aging. There were no significant changes in resting heart rate with aging, with a range of 66 bt.minâ »Â¹ to 74.86 bt.minâ »Â¹, therefore within normal ranges. Of the strength factors, age only affected shoulder and push strength significantly: Showing a decrease in shoulder strength from 49.89 kgF to 39.91 kgF in the men aged 20-29 to the 50-59 respectively and an increase in push strength from men aged 30-39 and 40-49 to those aged 50-59. Part II results revealed highly frequent lift rates and large degrees of sagittal flexion and lateral bending in all three tasks. These postures adopted for long durations are likely to lead to the development of musculoskeletal disorders. Heart rates of workers from the three tasks were significantly different and heart rates for two tasks were above the recommended 110 bt.minâ »Â¹. Similarly the body discomfort ratings of the three tasks differed, although a common trend was seen in that lower back pain was the most commonly reported area of discomfort in all tasks. South African manual materials handling males did not show the same responses to aging as men from industrially advanced countries, calling for further research into these differences. Due to the high risks of the three tasks assessed, future research and interventions are required to reduce the risk of injury in the assessed tasks.
Keywords: Age and employment -- South Africa; Labor -- Social aspects -- South Africa; Brickmaking -- South Africa -- Automation; Brickmaking -- Social aspects -- South Africa; Brick trade -- South Africa; Aging -- Social aspects -- South Africa; Aging -- Research